Neurogenesis drives hippocampal formation-wide spatial transcription alterations in health and Alzheimer's disease - Morrissey, Zachery D.; Kumar, Pavan; Phan, Trongha X.; Maienschein-Cline, Mark; Leow, Alex; Lazarov, Orly (Frontiers in Dementia, 2025)
The mechanism by which neurogenesis regulates the profile of neurons and glia in the hippocampal formation is not known. Further, the effect of neurogenesis on neuronal vulnerability characterizing the entorhinal cortex in Alzheimer's disease (AD) is unknown. Here, we used in situ sequencing to investigate the spatial transcription profile of neurons and glia in the hippocampal circuitry in wild-type mice and in familial AD (FAD) mice expressing varying levels of neurogenesis. This approach revealed that in addition to the dentate gyrus, neurogenesis modulates the cellular profile in the entorhinal cortex and CA regions of the hippocampus. Notably, enhancing neurogenesis in FAD mice led to partial restoration of neuronal and cellular profile in these brain areas, resembling the profile of their wild-type counterparts. This approach provides a platform for the examination of the cellular dynamics in the hippocampal formation in health and in AD.